-5(x-2)+8x=5x-6

Simple and best practice solution for -5(x-2)+8x=5x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-2)+8x=5x-6 equation:


Simplifying
-5(x + -2) + 8x = 5x + -6

Reorder the terms:
-5(-2 + x) + 8x = 5x + -6
(-2 * -5 + x * -5) + 8x = 5x + -6
(10 + -5x) + 8x = 5x + -6

Combine like terms: -5x + 8x = 3x
10 + 3x = 5x + -6

Reorder the terms:
10 + 3x = -6 + 5x

Solving
10 + 3x = -6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
10 + 3x + -5x = -6 + 5x + -5x

Combine like terms: 3x + -5x = -2x
10 + -2x = -6 + 5x + -5x

Combine like terms: 5x + -5x = 0
10 + -2x = -6 + 0
10 + -2x = -6

Add '-10' to each side of the equation.
10 + -10 + -2x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = -6 + -10
-2x = -6 + -10

Combine like terms: -6 + -10 = -16
-2x = -16

Divide each side by '-2'.
x = 8

Simplifying
x = 8

See similar equations:

| 36+7n=6(n+7) | | 13=7+21t-16t^2 | | 10-4j-7=-9-7j | | 2x+6=3+6x-7 | | -7625+185t=0 | | 2q=18.92+6.3q | | 13.9j-9.71-8.7=9.43+16.3j | | -4y=-3y-10 | | 7x+4(x-5)=3(x+2)-5 | | 8x-3y=14fory | | 2x+5+6x-1=90 | | 3+10q=6+9q | | 3/4z=-5+1/2 | | 19.03+11.2y=5.1y-17.59-9.13 | | 4(-6x+1)=20-8x | | 335=5x^3 | | 8x+5-2x=-(5x-x) | | 3/4z=-5.5 | | 14.7t-5.79=15t | | 9h-(2h-4h+1)=38-2h | | 15.7g+18.66+7.2g=19.5g-13.64 | | -3(5a+6)=-5a+22 | | 0.7x-0.1=0.6x+2 | | 15x=2(1+9x) | | 2/3x=44 | | (5/9x)-(1/3)=3 | | -6r+1=-7r+20 | | 30+3x=-(3x+6) | | 3(x-4)=4x+1 | | -7-9k=7-7k | | =2z^2+13z+15 | | (2/3x)+(4/3)=(-4/3) |

Equations solver categories